RESEARCH OF THE PROCESS OF RESTORATION OF DEGRADED SOLAR PANELS - ТРИХЛЄБ, А. С.; ПАНАСЮК, І. В. (Technologies and Engineering, 2023)
Purpose. Study of the recovery process of degraded solar panels to develop simplified methods for determining the location of degradation. Development of recommendations and equipment for the restoration of degraded solar panels. Methodology. Analytical study of literary sources, generalization of literary sources, observation, comparison, measurement, experiment, material modeling, physical modeling Findings. The causes of potentially induced degradation (PID) of solar panels are analyzed. It is determined that PID occurs due to small unwanted currents between the semiconductor on one side and the glass, anti-reflective coating (ARC), frame and mount on the other side. The degradation in performance is due to the migration of sodium ions from the glass plate through the encapsulation (usually EVA) and anti-reflective coating (ARC) into the cell. This occurs when the semiconductor in the cell takes on a negative potential with respect to the encapsulation and support structure. PID contributing factors are identified. Temperature and humidity contribute to PID, and the intensity of the effect increases depending on the position in the row. Conditions for avoiding or mitigating PID are formulated. The equipment for PID prevention and reversal is considered. Benches have been created to track the change in the current-voltage characteristic and restore degraded solar panels. A method for organoleptic determination of battery degradation sites has been developed. Recommendations for the restoration of solar panels in the field have been developed. Originality. The relationship between the contact of panels with fasteners and the intensity of their degradation was revealed. It was found that the parts of the panels that touched the fastening structure degraded more than other battery structures. These parts shunt other parts of the battery cells. Practical value. A method for organoleptic determination of battery degradation sites has been developed. Recommendations for the restoration of solar panels in natural conditions have been developed. It was determined that the panels, which had an increased potential relative to the ground, recovered faster than on the stand. Keywords: PID effect, degradation of solar panels, restoration of solar panels, method of organoleptic determination of degradation sites of solar panels.